2005
DOI: 10.1039/b414194f
|View full text |Cite
|
Sign up to set email alerts
|

Application of microchip assay system for the measurement of C-reactive protein in human saliva

Abstract: In the last decade, saliva has been advocated as a non-invasive alternative to blood as a diagnostic fluid. However, use of saliva has been hindered by the inadequate sensitivity of current methods to detect the lower salivary concentrations of many constituents compared to serum. Furthermore, developments in the areas related to lab-on-a-chip systems for saliva-based point of care diagnostics are complicated by the high viscosity and heterogeneous properties associated with this diagnostic fluid. The biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(171 citation statements)
references
References 48 publications
(74 reference statements)
7
163
1
Order By: Relevance
“…40 The mixer is compatible with viscosities corresponding to those of biological fluids that are of potential interest: the viscosity of human blood serum (y2 mPa s), 41 whole blood, which has a viscosity of approximately 5-6 mPa s at low rates of shear, 41 urine (y1 mPa s), 42 tears (2 to 9 mPa s), 43 and saliva (2 to 9 mPa s). 44 …”
Section: Efficiency Of Mixingmentioning
confidence: 99%
“…40 The mixer is compatible with viscosities corresponding to those of biological fluids that are of potential interest: the viscosity of human blood serum (y2 mPa s), 41 whole blood, which has a viscosity of approximately 5-6 mPa s at low rates of shear, 41 urine (y1 mPa s), 42 tears (2 to 9 mPa s), 43 and saliva (2 to 9 mPa s). 44 …”
Section: Efficiency Of Mixingmentioning
confidence: 99%
“…Although prior studies have reported that saliva can be used to measure biomarkers in patients with cardiovascular disease (CVD) and acute myocardial infarction (Christodoulides et al, 2005;Jones et al, 1994;Miller et al, 2010;Mirzaii-Dizgah & Jafari-Sabet, 2011), only one study of HF patients has examined salivary biomarkers. In a study comparing 40 outpatients with HF to 45 healthy controls, Offenbacher and Beck (2014) found that salivary N-terminal pro-BNP (NT-proBNP) had 82.2% sensitivity and 100% specificity for the presence of HF.…”
mentioning
confidence: 99%
“…In addition, saliva contains analytes at concentrations 1,000 times lower than in plasma (33). Thus, sensitive detection systems are required when using saliva as diagnostic material (9).…”
Section: Discussionmentioning
confidence: 99%